2014
DOI: 10.1002/term.1953
|View full text |Cite
|
Sign up to set email alerts
|

Combination of platelet-rich plasma within periodontal ligament stem cell sheets enhances cell differentiation and matrix production

Abstract: The longstanding goal of periodontal therapy is to regenerate periodontal tissues. Although platelet-rich plasma (PRP) has been gaining increasing popularity for use in the orofacial region, whether PRP is useful for periodontal regeneration is still unknown. The purpose of this study was to determine whether a mixture of periodontal ligament stem cell (PDLSC) sheets and PRP promoted bone regeneration, one of the most important measurement indices of periodontal tissue regenerative capability in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Defining the mechanisms involved in stem cell aging is important because reversal of this process can delay the effects of aging and enhance regeneration [63,64]. Accumulating data have demonstrated the positive effects of various biological agents and growth factor-including preparations on dental stem cells, suggesting the possibility to manipulate stem cells to enhance their therapeutic efficacy [23,25,65,66]. Given the pivotal role of the niche in determining stem cell functions, new anti-aging strategies have recently emerged to decrease the age-related dysfunction of stem cells, including, but not limited to, the treatment of cells with cyclin-dependent kinase inhibitors [67] and the modulation of cells by a young extrinsic microenvironment [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining the mechanisms involved in stem cell aging is important because reversal of this process can delay the effects of aging and enhance regeneration [63,64]. Accumulating data have demonstrated the positive effects of various biological agents and growth factor-including preparations on dental stem cells, suggesting the possibility to manipulate stem cells to enhance their therapeutic efficacy [23,25,65,66]. Given the pivotal role of the niche in determining stem cell functions, new anti-aging strategies have recently emerged to decrease the age-related dysfunction of stem cells, including, but not limited to, the treatment of cells with cyclin-dependent kinase inhibitors [67] and the modulation of cells by a young extrinsic microenvironment [26].…”
Section: Discussionmentioning
confidence: 99%
“…If cell sheet technology is used for cell delivery, the functionality of the cell sheets used in the trials, which may be influenced by the cell populations employed [21] as well as by the methods used for cell sheet production [23][24][25], must be predicted. Previously published data have demonstrated that the multipotent capacity and regenerative potential of human PDLSCs are severely compromised with increasing donor age [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…PRP has been used in recent times for management of intrabony defect [11], gingival recession [12], as a part of tissue engineering protocols [13]. A recent systematic review and meta analysis on the usefulness of autologous platelet concentrates on intrabony defect management revealed that PRP has a significant additive effect when used along with bone grafts for regeneration of intrabony defects [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the construction of a physiologically similar microenvironment to that which produces and maintains the periodontal ligament is important. Previous studies have focused on the change in the gene expression and protein secretion of the seed cells through gene transfection [47] or on the provision of beneficial environments to seed cells by using the cell culture supplements derived from plasma that is rich in growth factors [48] or conditioned medium derived from embryonic cells [49]. However, all these methods have limitations.…”
Section: Discussionmentioning
confidence: 99%